2020
DOI: 10.1039/d0gc01517b
|View full text |Cite
|
Sign up to set email alerts
|

p-Xylene from 2,5-dimethylfuran and acrylic acid using zeolite in a continuous flow system

Abstract: The continuous flow synthesis of p-Xylene (pXL) via Diels-Alder cycloaddition of lignocellulosic biomass-derivable 2,5-dimethylfuran (DMF) and acrylic acid (AA) was performed over different type of zeolites, i.e. Beta, ZSM-5 and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Additionally, Toste, and more recently Al‐Naji and co‐workers have rendered acrolein and acrylic acid as viable dienophiles for DA+decarboxylation‐dehydration with DMeF [22,26] . Continuous flow synthesis of DMeF from HMF using Ni on N ‐doped carbon [27] followed by reaction with acrylic acid over a β‐zeolite system have also been used to produce p‐ xylene in good yields (up to 83 %) [26a] . However, even these novel methods fail to utilize furfurals as the core platform for DA‐aromatization.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Toste, and more recently Al‐Naji and co‐workers have rendered acrolein and acrylic acid as viable dienophiles for DA+decarboxylation‐dehydration with DMeF [22,26] . Continuous flow synthesis of DMeF from HMF using Ni on N ‐doped carbon [27] followed by reaction with acrylic acid over a β‐zeolite system have also been used to produce p‐ xylene in good yields (up to 83 %) [26a] . However, even these novel methods fail to utilize furfurals as the core platform for DA‐aromatization.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] A transition toward more sustainable and renewable resources and production processes for energy and commodities is in great demand. [5][6][7][8][9][10][11] Among the renewable resources, lignocellulosic biomass (LCB) is one of the most promising feedstock since it is abundant, cheap, and intrinsically sustainable as it is produced via photosynthesis by plants. [12][13][14] LCB is a complex solid composite, made by three biopolymers: cellulose, hemicellulose, and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…64,65 All these studies were performed in batch systems, which presents disadvantages when compared to continuous flow systems, e.g., complex product-catalyst separation, time, energy-consumption in discontinuous steps and cost efficiency . 10,12,59,66,67 Horáček et al 52 only reported the LS fragmentation in a continuous flow system at a high reaction temperature (320°C) over bimetallic Ni and Mo catalyst supported on Al 2 O 3 . In this study and due to over hydrogenation, guaiacol was found the major product of LS catalytic fragmentation (yield higher than 1.8 wt.-%).…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization of molecular catalysts with known high activity on solid supports makes their recyclability accessible in industry and is one strategy to overcome their troublesome recovery. The potential of catalysis is oen limited by the scale up necessary for industrial application and this is particularly the case in biorenery, [1][2][3][4][5] which is an approach geared towards upgrading lignocellulosic biomass to valued-added chemicals in the so-called biorenery processing. 3,6 Within this process, lignocellulosic biomass undergoes physico-chemicals transformation toward low-carbon footprint ne products.…”
Section: Introductionmentioning
confidence: 99%